A CULTURAL DIMENSION APPROACH TO ENVIRONMENT AND DEVELOPMENT PROMOTING SUSTAINABLE DEVELOPMENT IN VIETNAM - Bach Tan Sinh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Until recently, research on institutions promoting sustainable development in Vietnam has mainly focused on the role of the state and business - the two main groups of social actors involved in shaping the development path of Vietnam. The article analyzes the cultural conflict between three groups of social actors (state, business and civil society) on the path of sustainable development in Vietnam from cultural perspectives on environment and development. The article argues that the cultural approach to environment and development is considered as a new approach different from the traditional approach, will provide a new perspective on the dynamics of policy related to the environment and development, which has been implemented together with sustainable development in Vietnam. Code: 23011601